Induction of Broad Immunity against Invasive Salmonella Disease by a Quadrivalent Combination Salmonella MAPS Vaccine Targeting Salmonella Enterica Serovars Typhimurium, Enteritidis, Typhi, and Paratyphi A - Emily M. Boerth; Joyce Gong; Becky Roffler; Claudette M. Thompson; Boni Song; Sasha F. Malley; Angelika Hirsch; Calman A. MacLennan; Fan Zhang; Richard Malley; Ying-Jie Lu (Vaccines, 2023)
Bloodstream infections in low- and middle-income countries (LMICs) are most frequently attributed to invasive Salmonella disease caused by four primary serovars of Salmonella enterica: Typhi, Paratyphi A, Typhimurium, and Enteritidis. We showed previously that a bivalent vaccine targeting S. Typhi and S. Paratyphi A using a Multiple Antigen-Presenting System (MAPS) induced functional antibodies against S. Typhi and S. Paratyphi. In the current study, we describe the preclinical development of a first candidate quadrivalent combination Salmonella vaccine with the potential to cover all four leading invasive Salmonella serotypes. We showed that the quadrivalent Salmonella MAPS vaccine, containing Vi from S. Typhi, O-specific Polysaccharide (OSP) from S. Paratyphi A, S. Enteritidis and S. Typhimurium, combined with the Salmonella-specific protein SseB, elicits robust and functional antibody responses to each of the components of the vaccine. Our data indicates that the application of MAPS technology to the development of vaccines targeting invasive forms of Salmonella is practical and merits additional consideration.